229k views
1 vote
PLZZZZZ HELP ME ITS TIMED

Which pair shows equivalent expressions?
A. 3(x + 2) = 3x + 6
B. 3x + 2x = x²(3+2)
C. 3x+2 = 3 (x+2)
D. -3(2+x) = -6x - 3

2 Answers

7 votes

Answer:

A

Explanation:

Took test

User Greycon
by
5.9k points
1 vote

Answer:

A.
3(x+2) = 3x+6

Explanation:

Lets look at each of these

A


3(x+2) = 3x+6\\\\3x+6=3x+6

B


3x+2x=x^2(3+2)\\\\3x+2x=5x^2

C


3x+2=3(x+2)\\\\3x+2=3x+6

D


-3(2+x)=-6x-3\\\\-6-3x=-6x-3

As we can see, A was the only option that simplified to equal itself, so that is our answer.

User Srayner
by
5.8k points